Policy Science at an Impasse: A Matter of Conceptual Stretching?. Issue 2 (April 2017) - Carlsson, Lars
Abstract : Policy science, particularly the policy network approach, is teeming with new studies and concepts. This abundance has resulted from the inescapably multidisciplinary approach of policy science and from our ambition to surpass traditional policy analysis. The field's concepts are developing so rapidly, however, that new hybrids and mutations threaten us with confusion and overcomplication rather than providing us with clarity, and cumulative improvement and theory development are thus hampered. These unintended consequences are intimately associated with errors of conceptual stretching, that is, using valuable concepts with clear meaning to refer to inapplicable phenomena, thus misusing and diminishing the value of our conceptual tools. In policy science, this is also the case with central analytic tools, frameworks, models, and theories. Therefore, although policy making can be messy, if we hope to escape the alleged impasse in policy science, we cannot afford to tolerate the current inaccuracies of conceptual stretching. Related Articles: Raile, Eric D., Amber N. W. Raile, Charles T. Salmon, andLori Ann Post .2014 . "Defining Public Will ."Politics & Policy 42 (1 ):103 ‐130 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12063/full Shanahan, Elizabeth A., Mark K. McBeth, andPaul L. Hathaway .2011 . "Narrative Policy Framework: The Influence of Media Policy Narratives on Public Opinion ."Politics & Policy 39 (3 ):373 ‐400 .http://onlinelibrary.wiley.com/doi/10.1111/j.1747-1346.2011.00295.x/full Gruber, Lloyd. 2013 . "Trade, Growth, Poverty, and Politics: Toward a Unified Theory ."Politics & Policy 41 (5 ):723 ‐764 .http://onlinelibrary.wiley.com/doi/10.1111/polp.12034/full